Ultrasound-assisted leaching of spent lithium ion batteries by natural organic acids and H2O2. (September 2020) - Esmaeili, M.; Rastegar, S.O.; Beigzadeh, R.; Gu, T.
Abstract: Ultrasound-assisted bioacid leaching was examined for the extraction of valuable metals from spent lithium ion batteries (LIBs). In this work, organic acids in lemon juice were used as the leaching agent together with H2 O2 . Three effective factors, namely solid/liquid (S/L) ratio, lemon juice percentage, and H2 O2 volume percentage, were optimized using Response Surface Methodology (RSM). The optimal conditions were found to be 0.98% (w/v) S/L ratio, 57.8% (v/v) lemon juice and 8.07% (v/v) H2 O2 in the leaching liquor, achieving recovery of 100% Li, 96% Co and 96% Ni. Furthermore, the individual effects of ultrasound, H2 O2 and lemon juice on metal recovery were studied and the results showed that without H2 O2 or lemon juice, the metal recovery rates decreased greatly while the absence of ultrasound reduced recovery rates to a much smaller extent, indicating that both H2 O2 and lemon juice were essential in the leaching process. The effect of time on the metals recoveries was examined and results showed that Li and Co recovery reached 100% with the leaching time of 35 min. The modified shrinking core modeling results suggested that chemical reaction was the rate controlling step. Highlights: Organic acids in lemon juice were used as leaching agents. Ultrasound and H2 O2 were used to assist the leaching of lithium ion batteries (LIBs). The kinetics of the key leaching reactions was investigated. Optimization of effective factors was done using Response Surface Methodology (RSM).